Pengaruh Pendidikan Kesehatan Ibu Hamil terhadap Pengetahuan Ibu tentang Gizi Balita Usia 1-5 Tahun di Klinik Eva Mulia Grogol Jakarta Barat Tahun 2024 - Theresia Eci Pratiwi; Wiwin Widyastuti (Universitas Pahlawan Tuanku Tambusai, 2025)
Basic immunization for infants is an important step in preventing serious diseases that can endanger the child's life. However, although the benefits are clear, the completeness of immunization is often hampered by the mother's knowledge and attitude towards immunization. Adequate knowledge about the benefits of immunization can shape the mother's positive attitude, which in turn increases the completeness of immunization. On the other hand, ignorance or negative attitudes towards immunization can hinder timely vaccination.To determine the relationship between knowledge and attitudes of mothers about basic immunization and the completeness of basic immunization in 1-year-old infants at the Sawarna Village Integrated Health Post in 2024.The sample size in this study used a total of 50 mothers with 1-year-old infants based on secondary data from those registered at the Sawarna Village Integrated Health Post from October to December 2024 which was taken by total sampling. The data analysis used was univariate and bivariate analysis using the chi square test, if it did not meet the requirements, it would be continued with the fisher exact test. there is a relationship between knowledge and attitudes of mothers about basic immunization and the completeness of basic immunization in 1-year-old infants with a p value = 0.000. Educate family members or other parents about the importance of immunization. Family support is very important to strengthen the mother's decision to provide immunization.